Nutrition and diet in rheumatoid arthritis, axial spondyloarthritis, and psoriatic arthritis: a systematic review - Van den Bruel, Kaat; Kulyk, Myroslava; Neerinckx, Barbara; De Vlam, Kurt (Frontiers in Medicine, 2025)
IntroductionThis systematic review aimed to evaluate the effects of specific diets, dietary supplements, and probiotics on disease activity, inflammation, and immune response in patients with rheumatoid arthritis (RA), axial spondyloarthritis (axSpA), and psoriatic arthritis (PsA).MethodsA systematic literature search was conducted in PubMed, Embase, and the Cochrane Library. Randomized clinical trials (RCTs) of patients with RA, axSpA, or PsA undergoing dietary or nutritional interventions were included. Duplicates were removed using EndNote and Rayyan, and study quality was assessed with the Academy of Nutrition and Dietetics Quality Criteria Checklist for Primary Research. Outcomes of interest were changes in immune response, inflammatory biomarkers, and disease activity.ResultsFrom 2,250 screened articles, 49 studies met the inclusion criteria. In RA, vegan, anti-inflammatory, and Mediterranean diets improved disease activity, inflammation markers, and quality of life. For axSpA, evidence was limited, though supplementation with polyunsaturated fatty acids (PUFAs) showed potential benefits. Across conditions, nutritional supplements such as PUFAs, vitamin D, pomegranate extract, and ginger demonstrated anti-inflammatory and immunomodulatory effects. Probiotics and synbiotics had variable impacts, with synbiotics reducing interleukin-17 (IL-17) levels. In PsA, a hypocaloric diet supplemented with omega-3 fatty acids was associated with reduced disease activity.DiscussionDietary interventions and supplementation may support the management of chronic arthritis through modulation of inflammatory and immune pathways. However, due to heterogeneity in study designs, interventions, and outcomes, a meta-analysis was not feasible, and results were synthesized narratively. While findings suggest potential benefits as adjuncts to pharmacological treatment, further high-quality RCTs are required to confirm long-term clinical efficacy.Systematic review registrationThe systematic review is registered in PROSPERO under ID CRD420251010982. https://www.crd.york.ac.uk/PROSPERO/view/CRD420251010982.